PENTINGNYA PERAN PENYULUHAN DALAM PENCEGAHAN STUNTING: EDUKASI PADA KADER POSYANDU DI DESA KARANGANYAR KABUPATEN SEMARANG - Hasanah, Mufidatul; Sari, Anisa Lidya; U'yuna, Virda Qorri (ALKADIMAT, 2024)
Stunting is a developmental disorder experienced by children due to poor nutrition, repeated interactions and inadequate stimulation. Indonesia is one of the countries that still faces nutritional problems that have a serious impact on the quality of human resources. It is necessary to conduct education related to the prevention of stunting and check children’s growth regularly at the nearest posyandu. The community service aims to provide education and determine the level of understanding of posyandu cadre and the local community regarding stunting prevention. This community service activity is provided through counseling in stunting prevention: education for posyandu cadres in Karanganyar Village. This activity was carried out on February 20,2024 which was attended by posyandu cadres from each hamlet and some village officials. The results of the analysis show that almost all posyandu cadres and the community have understood tips for preverenting stunting in children.